Unrecognized Congenital Heart Disease in Pregnancy Presenting as Eisenmenger Syndrome with Severe Preeclampsia and Intrauterine Fetal Death: A Case Report - Marsha Marvella; Muhammad Alamsyah Aziz; Adhi Pribadi; Charlotte Johanna Cool (Dep/SMF Obstetri & Ginekologi Fakultas Kedokteran Universitas Padjadjaran, 2026)
Introduction: Undiagnosed congenital heart disease (CHD) during pregnancy can lead to catastrophic outcomes by exacerbating cardiovascular stress. This case describes a fatal presentation of Eisenmenger syndrome in a pregnant patient, initially misdiagnosed as bronchial asthma, resulting from a combination of a large secundum Atrial Septal Defect (ASD) and a Patent Ductus Arteriosus (PDA).Case Presentation: A 27-year-old primigravida at 26 – 27 weeks’ gestation presented with severe preeclampsia, Eisenmenger syndrome, and severe pulmonary arterial hypertension (mWHO Class IV), complicated by intrauterine fetal death (IUFD). The patient reported progressive dyspnea and cyanosis, previously misattributed to asthma. Transthoracic echocardiography revealed a large secundum ASD and PDA, with significant right-heart enlargement and severe pulmonary hypertension. Despite multidisciplinary intensive management, including supplemental oxygen, diuretics, sildenafil, nitroglycerin, inhaled iloprost, and inotropic support, the patient developed acute decompensated right heart failure postpartum and succumbed to cardiogenic shock.Conclusion: Unexplained dyspnea and cyanosis during pregnancy necessitate immediate and comprehensive cardiovascular evaluation. Eisenmenger syndrome is associated with exceptionally high maternal mortality. Early recognition, rigorous preconception counseling, and specialized multidisciplinary care are imperative to mitigate the risk of fatal outcomes in this high-risk population.Penyakit Jantung Bawaan yang Tidak Terdiagnosis pada Kehamilan yang Bermanifestasi sebagai Sindrom Eisenmenger dengan Preeklamsia Berat dan Kematian Janin Intrauterin: Laporan KasusAbstrakPendahuluan: Penyakit jantung bawaan yang tidak terdiagnosis pada kehamilan dapat menyebabkan komplikasi fatal akibat perubahan fisiologis kardiovaskular. Kasus ini menyoroti presentasi fatal sindrom Eisenmenger pada kehamilan yang awalnya salah didiagnosis sebagai asma bronkialPresentasi Kasus: G1P0A0 usia 27 tahun gravida 26 – 27 minggu datang dengan preeklamsia berat, sindrom Eisenmenger, hipertensi pulmonal berat (mWHO IV), dan intrauterine fetal death. Pasien mengalami dispnea progresif dan sianosis selama kehamilan yang awalnya salah didiagnosis sebagai asma bronkial. Ekokardiografi menunjukkan ASD besar dan PDA disertai hipertensi pulmonal berat. Meskipun telah dilakukan penatalaksanaan intensif baik farmakologis maupun suportif, pasien mengalami gagal jantung kanan akut dekompensasi pascapersalinan dan meninggal akibat syok kardiogenik.Kesimpulan: Dispnea dan sianosis persisten selama kehamilan harus menjadi indikasi dilakukan evaluasi kardiovaskular menyeluruh segera. Sindrom Eisenmenger memiliki angka mortalitas maternal yang sangat tinggi, sehingga menekankan pentingnya diagnosis dini, konseling prakonsepsi, serta tata laksana multidisiplin khusus pada kehamilan risiko tinggi.